2005
DOI: 10.1088/1464-4258/7/6/020
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining sub-pixel alignment for a single-camera two-bucket shearing speckle interferometer

Abstract: In a phase stepped speckle interferometer, phase steps can be realized temporally or spatially. The spatial approach has the advantage of simultaneous acquisition of all phase stepped interferograms which eliminates phase errors due to phase changes that can occur between phase steps when phase is stepped in time. For spatially phase stepped systems based on multiple optical channels, it is important that interferograms are well aligned to the others. Alignment can be achieved and maintained by a system that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…4(ii). We note that in this figure the location of the optical axis is at index (3,4), and not at index (3,3) as expected. This is due to the fact that the centre of the optical axis may actually be located outside the active area of the camera for the first iteration of the algorithm.…”
Section: Algorithmsupporting
confidence: 77%
See 1 more Smart Citation
“…4(ii). We note that in this figure the location of the optical axis is at index (3,4), and not at index (3,3) as expected. This is due to the fact that the centre of the optical axis may actually be located outside the active area of the camera for the first iteration of the algorithm.…”
Section: Algorithmsupporting
confidence: 77%
“…Relative optical alignment, in an interferometer for example, can be achieved by iteratively measuring the peak correlation value between two laterally displaced speckle fields [4] . These speckle fields originate from the same object, but are displaced with respect to each other if the paths they travel are not exactly co-incident on the same plane where they recombine prior to capture by a digital camera.…”
Section: Introductionmentioning
confidence: 99%
“…Mirrors M3 and M4 are set to a position for which the imaging system projects two images of the object side by side onto the CCD camera. Mirror M4 can be fine-adjusted by piezo-elements for sub-pixel alignment of the two images [13]. As a result two speckle interferograms are obtained side by side on a single CCD camera, with a mutual phase step of π/2.…”
Section: Methodsmentioning
confidence: 99%
“…Another system that employs spatial phase shifting involves a polarization-based shearing interferometer which divides an incoming image into two and images them side-by-side on a camera with a π relative phase shift [70]. Analysis showed that maintaining sub-pixel image registration was essential to maintain accurate measurements [71]. A more recent paper [70] discusses an improvement of the system when dealing with unfavourable polarization states.…”
Section: Spatial Phase Steppingmentioning
confidence: 99%